Delight in one thousand characters : the classic manual of East Asian calligraphy - Zhiyong; O'Leary, Susan, 1950-; O'Leary, Susan, 1950-; Tanahashi, Kazuaki, 1933-; Tanahashi, Kazuaki, 1933-; Zhou, Xingsi, -521 (Shambhala Publications, Inc., 2022)
"An esteemed masterpiece, the One Thousand Character Essay embodies the philosophy, mythology and history of ancient China. The Essay was composed by the literary giant Zhou Xingsi in the sixth century as a rhymed composition with no repeated ideographs. It has been sung to infants as a lullaby, functioned to teach language and writing, used as library index codes and as signs for seating applicants for examinations selecting public officials. The One Thousand Character Essay provides a window into the social values of the times and the importance of nature in defining the individual's and society's relation to the larger world. It refers to and draws on the meaning of the writing of Confucius, Laozi, Mengzi, Mozi, and Zhuangzi, the essential ancient Chinese writers. As the Essay reflects core values in Chinese civilization throughout time and gives insight into its major early writers, it can be a fundamental text in studying Chinese classical works. Its influence extended to Korea, Japan, Vietnam, and beyond"--